2016
DOI: 10.15298/arctoa.25.29
|View full text |Cite
|
Sign up to set email alerts
|

Liverworts of Putorana Plateau (East Siberia): an updated checklist

Abstract: The new checklist of Putorana liverworts was compiled based on examination of recent collections and summarizing of literature data. It includes 118 species, 47 of them are new for the plateau. The most interesting records are Odontoschisma francisci, Saccobasis polymorpha, Endogemma caespiticia and Marchantia romanica. The occurrence of 26 taxa mentioned in the literature was not re-confirmed. In general terms, the flora is typical for continental Hemiarctic with very limited number of taxa showing East Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The erosion of edges of these layers resulted in alternation of flat terracelike surfaces and steep rocky slopes featuring trappean structure of slopes with several levels. For the western part of the plateau, deep narrow lake depressions of tectonic origin with steep rocky slopes are typical [15].…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The erosion of edges of these layers resulted in alternation of flat terracelike surfaces and steep rocky slopes featuring trappean structure of slopes with several levels. For the western part of the plateau, deep narrow lake depressions of tectonic origin with steep rocky slopes are typical [15].…”
Section: Study Sitementioning
confidence: 99%
“…The Putorana Plateau, which is situated in the NW part of the Central Siberian Tableland, belongs to the regions sensitive to shifts in atmospheric circulation [15,16]. It represents a unique territory with a set of subarctic and arctic ecosystems in an isolated mountain range.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presented research focused on the SOC concentration and its association with important biophysical factors and soil weathering products on extended, variably steep slopes of the vast and remote Putorana Plateau, one of the least investigated subarctic areas. The basaltic plateau encompasses approximately 250,000 km 2 in the NW part of the Central Siberian Tableland 22 . Spatial correlation between SOC and Fe and Al oxide and hydroxide concentrations identified in an adjacent section of the Yenisei River basin 23 showed that secondary Fe and Al minerals could promote SOC stabilization in the adjacent Putorana massif itself.…”
Section: Introductionmentioning
confidence: 99%
“…In Asia the species is not rare in mountains in oceanic and suboceanic areas of Far East of Russia, particularly in Chukotka Autonomous Areas and Kamchatka Territory (Konstantinova et al, 2009;Bakalin, 2010) and occurs scattered in humid areas of mountains of South (Váňa & Ignatov 1995;Konstantinova et al, 2003) and Baikal Siberia (authors' unpublished data, see specimens examined), where it probably is not rare in appropriate localities. In the north of Asia the species is found in single localities on eastern slopes of Urals (Storozheva, 1986, Konstantinova & Lapshina, 2017, on Putorana Plateau (Bakalin et al, 2016) and several localities in the Taimyr Peninsula (KPABG, isling.org/hepatics). The species is probably more widespread in poorly studied northern and mountain regions of Asia and will be found more to be common in future studies.…”
mentioning
confidence: 99%